Imaging a Decratonized Lithosphere: A Case of the Eastern North China Craton - Hongqiang Li; Xingfu Huang; Rui Gao; Ramon Carbonell; Lei Gao (Geophysical Research Letters)
Abstract During decratonization, the cratonic lithosphere mantle experienced composition transformation and thinning, which have been extensively studied in the North China Craton. Yet, modification from refractory lithospheric mantle to fertile one remains enigmatic due to a shortage of seismically resolvable data on the lithospheric internal structures. New high‐resolution normal incidence seismic reflection transect documents: coexistence of two lithospheric mantles with different reflection characteristics, lithosphere‐scale domes, boudinage upper‐crust, and Cenozoic faulted basins. Reflective and transparent mantles are interpreted to represent the cratonic and the newly formed lithospheric mantles, respectively. The irregular contact boundaries between the ancient and newly formed lithospheric mantles are revealed as channel‐like structures within the mantle, which possibly provide pathways for the rise of melts and/or fluids from the deep mantle. The deep melts/fluids rising through the channel‐like structures are key elements that enable generation of the newly formed lithospheric mantle, and provide means for the modification of cratonic lithospheric mantle.